The Influence of Core Resources and Critical Resources on Customer Value on MSMEs Palm Sugar Products - Nurjaya Nurjaya (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of core resources and critical resources on customer value at MSMEs Palm Sugar Products. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study, core resources have a significant effect on customer value by 9.2%; the hypothesis test is obtained t count> t table or (5.504> 1.968). Critical resources significantly affect customer value by 10.4%; hypothesis testing is obtained t count> t table or (5.891> 1.968). Simultaneously, core resources and critical resources have a significant effect on customer value with the regression equation Y = 37.234 + 0.164X1 + 0.203X2, and the influence contribution is 14.7%,